Ketamine Infusions for Outpatient Pain Management: A Policy Development Project. Issue 5 (September 2018) - Allen, Cheryl A.; Conner, Ruth; Ivester, Julius R.
Abstract : Current literature supports using ketamine for both acute and chronic pain management. It is imperative that the development of evidence-based protocols and policies keep pace with health care delivery to ensure patient safety. This project's objective was to formulate an outpatient ketamine infusion policy that promotes consistent and evidence-based care within a specified hospital system. This policy addresses potential side effects and minimization of adverse events by addressing patient selection, level of nursing care required, appropriate monitoring, and staff education.